Natural Products-Based Metallic Nanoparticles as Antimicrobial Agents - Susanti, Deny; Haris, Muhammad Salahuddin; Taher, Muhammad; Khotib, Junaidi (Frontiers in Pharmacology, 2022)
Natural products offer a wide range of bioactivity including antimicrobial properties. There are many reports showing the antimicrobial activities of phytochemicals from plants. However, the bioactivity is only limited due to multidrug resistant properties of the microorganism and different composition of cell membrane. The antibacterial activity of the natural products is different toward Gram-negative and Gram-positive bacteria. These phenomena are caused by improper physicochemical conditions of the substance which hinder the phytochemical bioactivity against the broad range of bacteria. One of the strategies to improve the antimicrobial cation is by encapsulating the substance with nanoparticles. The most effective nanoparticle that improved the antimicrobial activities of the compounds or extract was using metallic nanoparticles (NPs) such as silver nanoparticles (AgNPs), gold nanoparticles (AuNPs) and platinum nanoparticles (PtNPs). Those metallic nanoparticles remarkably express synergistic effects against the microorganisms tested by affecting bacterial redox balance, thus disrupting their homeostasis. In this paper, we discuss the type of metallic nanoparticle which have been used to improve the antimicrobial activity of plant extract/constituents, preparation or synthesis process and characterisation of the plant-based metallic nanoparticles.